1987
DOI: 10.1080/09553008714552221
|View full text |Cite
|
Sign up to set email alerts
|

125IdUrd-induced Chromosome Fragments, Assayed by Premature Chromosome Condensation, and DNA Double-strand Breaks Have Similar Repair Kinetics in G1-phase CHO-cells

Abstract: The effect of 125I-decay on cell lethality, and induction of chromosome and DNA damage, was studied in synchronous non-cycling, G1-phase CHO-cells. For this purpose a population of mitotic cells was allowed to divide and progress through S-phase in the presence of 125IdUrd. Cells were subsequently transferred to conditioned medium (C-med) obtained from plateau-phase cultures that allowed cells to divide and accumulate in G1-phase in a non-cycling state. To accumulate 125I-induced damage, cells were kept frozen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…Despite the discrepancy in initial yields, however, there are strong correlations between measured radiation-induced dsbs and PCC breaks. The rejoining kinetics for PCC breaks and DNA dsbs are similar (10), and in addition radiosensitive mutants with defects in dsb rejoining show deficiencies in rejoining PCC breaks (11,12). Such results strongly suggest that DNA dsbs are indeed the primary initial…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Despite the discrepancy in initial yields, however, there are strong correlations between measured radiation-induced dsbs and PCC breaks. The rejoining kinetics for PCC breaks and DNA dsbs are similar (10), and in addition radiosensitive mutants with defects in dsb rejoining show deficiencies in rejoining PCC breaks (11,12). Such results strongly suggest that DNA dsbs are indeed the primary initial…”
Section: Introductionmentioning
confidence: 89%
“…Since the resolution of the assay used here is much higher, on the order of 100 kbp, this difference is perhaps not surprising. However, it must also be considered in this connection that the experiments for quantitating dsb misrejoining frequencies in this study were necessarily performed at much higher doses than experiments scoring chromosomal aberrations, which are typically 10 Gy or less. The possibility that fidelity of dsb rejoining varies with dose remains, although no dose effect was detected between 80 and 160 Gy in this study, and measurements of mutation frequency have suggested a linear dose-response relationship even to very low doses (21).…”
Section: Introductionmentioning
confidence: 99%
“…Mitotic cells were routinely frozen for later use by a method that optimally preserves cell integrity (Borrelli et al . 1987, Iliakis et al 1987 . The experiments described here were performed with cells that were on subculture 41 on the day of roller bottle preparation .…”
Section: Cell Synchronymentioning
confidence: 97%
“…The DNA DSBs induced by X-rays are repaired by the time these cells reach the first postirradiation mitosis. However, the repair is error-prone, leading to structural chromosomal aberrations (Lliakis et al, 1987). Experimental evidence suggests that DNA DSBs are among the primary lesions responsible for the induction of chromosome aberrations and cell death in mammalian cells (Bryant, 1985(Bryant, , 1988.…”
Section: Discussionmentioning
confidence: 99%